Teaching science - Levinson, Ralph, 1951- (London ; New York : Routledge in association with the Open University, 1994)
Science education has undergone far-reaching changes in the last fifty years. The articles collected together in this reader examine how we have reached our present consensus and what theories we now use to explain how children learn science. The central sections of the reader examine how all this can be translated into effective and stimulating teaching, how learning can be most accurately and fairly assessed and how the impact of gender, ethnicity and other factors on children's performance can be addressed in methods of teaching which make science accessible to all. The articles in the fina.
INTRODUCTION: WHY ASSESS?AN OVERVIEW OF NATIONAL ASSESSMENT SYSTEMS; 11-16; Assessment post-16; PRINCIPLES OF EFFECTIVE ASSESSMENT; Starting from aims and objectives; Using an assessment instrument which is appropriate for the purpose; Managing effective assessment; Sensible record keeping; EVALUATION; REFERENCES; Chapter 13 Gender differences in pupils' reactions to practical work; INTRODUCTION; GENDER DIFFERENCES IN ACHIEVEMENT-THE INTERNATIONAL SCENE; DIFFERENCES IN EXPERIENCE; DIFFERENCES IN WAYS OF EXPERIENCING; DIFFERENCES IN PROBLEM PERCEPTION; PUPIL-FRIENDLY PRACTICAL WORK?; SUMMARY.
Includes bibliographical references and index.
Print version record.
Keywords: Education; Science -- Study and teaching (Secondary); EDUCATION -- Teaching Methods & Materials -- Science & Technology; Education; Science -- Study and teaching (Secondary); Education; Science -- Study and teaching (Secondary); Secondary schools -- Curriculum -- Science; Electronic books